2021
DOI: 10.3390/fib9110071
|View full text |Cite
|
Sign up to set email alerts
|

Tensile, Flexural, and Morphological Properties of Jute/Oil Palm Pressed Fruit Fibers Reinforced High Density Polyethylene Hybrid Composites

Abstract: The incorporation of materials that were formally regarded as agricultural wastes into polymeric matrix has drawn the attention of many researchers in recent years. This research focused on reinforcing high-density polyethylene (HDPE) matrix with treated jute fiber (JF)/oil palm pressed fruit fibers (OPPFF) at varying weight proportions. JF and OPPFF were cut to 2.5 mm length and were chemically treated thereafter with 1 M and 1.5 M sodium hydroxide solution respectively. The composites were produced using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…In addition to modifying the lumens, alkaline treatment leads to the partial removal of lignin and surface impurities (63), which are hydrophilic components of the fiber (hydroxyl groups -OH) with greater water absorption capacity. Indeed, the crystallinity index (CI) obtained from X-ray diffraction analysis, shown in Figure 8, indicates that the natural fiber had a CI value of 60.75%, consistent with findings in other studies (64,65), while the fiber subjected to alkaline treatment showed a CI value of 66.22%.…”
Section: Effect Of Treatment On the Properties Of Jute Fibersmentioning
confidence: 99%
“…In addition to modifying the lumens, alkaline treatment leads to the partial removal of lignin and surface impurities (63), which are hydrophilic components of the fiber (hydroxyl groups -OH) with greater water absorption capacity. Indeed, the crystallinity index (CI) obtained from X-ray diffraction analysis, shown in Figure 8, indicates that the natural fiber had a CI value of 60.75%, consistent with findings in other studies (64,65), while the fiber subjected to alkaline treatment showed a CI value of 66.22%.…”
Section: Effect Of Treatment On the Properties Of Jute Fibersmentioning
confidence: 99%
“…Polyester is regarded as a worthy material for automotive design due to its inexpensive cost 2,3 .In recent studies, additives are sourced and incorporated into polymer matrices using various processes to improve their properties [4][5][6][7] . Ceramic or synthetic fibers or particles are often being utilized as the additives with proven results [7][8][9][10] . Natural-derived ones, on the other hand, are more cost-effective.…”
mentioning
confidence: 99%